Development and validation of assessment instrument for the perception and attitude toward tuberculosis among the general population in Indonesia: a Rasch analysis of psychometric properties - Pitaloka, Dian Ayu Eka; Kusuma, Ikhwan Yuda; Pratiwi, Hening; Pradipta, Ivan Surya (Frontiers in Public Health, 2023)
Introduction: Tuberculosis (TB)-related knowledge is an important evaluation metric for health education interventions. Factor analysis is limited when used on ordinal scales and does not provide in-depth item function examinations, whereas Rasch analysis addresses these limitations and offers potential advantages such as generalizability, testing of unidimensionality, producing an ordered set of items, and identifying poorly functioning items. Therefore, this research aims to develop a reliable and valid measure of perception and attitude toward TB (PATT) for public application use Rasch Analysis.Methods: A questionnaire-based survey was conducted on the Indonesian general population using the Google Form platform. Rasch analysis was then employed to examine the psychometric properties and develop the final items of PATT.Results: Experts from across the TB community participated in the PATT development, producing an initial scale of 16 items. Up to 1,616 participants completed the PATT questionnaire, where 74.8% were female, and 5% had a TB history. The final unidimensional 16-item scale has an item reliability of 1.00 for the two components (perception and attitude), a person reliability index of 0.87 and 0.60, as well as a Cronbach's test reliability of 0.88 and 0.88 for perception and attitude, respectively.The PATT is a unidimensional scale with good construct validity and internal consistency. It has the potential to be useful for the assessment of TB perception and attitude in research and clinical practice.